Asymmetric Impacts of Rainfall Anomalies on Banking Credit Performance Across Customer Segments - Roman Christopher Yudhistira; Jagat Prirayani (Journal of Economics and Business UBS, 2026)
The modern banking sector, particularly in emerging-market economies such as Indonesia, is increasingly exposed to nontraditional exogenous shocks, especially physical climate risks. For PT Bank XYZ, a systemically important State-Owned Enterprise (KBMI 4) bank with extensive grassroots penetration, extreme weather events directly threaten operational continuity and the repayment capacity of its vulnerable debtor base. While traditional literature evaluates credit portfolios through an aggregated macroeconomic perspective, this study comprehensively investigates the asymmetric impacts of physical climate risk—operationalized through monthly rainfall anomalies—on outstanding loan volumes across distinct borrower segments. To minimize aggregation bias and distinguish genuine business cycle effects from pandemic-induced supply chain disruptions, the portfolio was decomposed into Micro, Consumer, Retail, and Corporate segments using contiguous post-pandemic monthly time-series data from January 2022 to December 2025. Methodologically, the study employed separate autoregressive integrated moving average (ARIMA) (1,0,0) models with semirobust standard errors while controlling for inflation, benchmark interest rates, and economic confidence indices. The empirical estimations revealed a significant phenomenon termed the “Weather Paradox”: extreme rainfall did not immediately reduce outstanding credit in the Micro and Retail segments; instead, it appeared to trigger precautionary borrowing behavior and emergency digital credit drawdowns. Conversely, the Corporate and Consumer loan portfolios demonstrated strong institutional resilience to localized weather shocks. Furthermore, financial literacy was found to function as an effective cognitive risk buffer that mitigated these ecological pressures, preventing localized climate-related distress from escalating into systemic credit defaults. These findings provide important implications for climate-adjusted credit risk management and financial inclusion policies within emerging-market banking systems.